1999
DOI: 10.1007/s004240051059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of the small Ca 2+ -regulated K + channel (rSK4) of colonic crypts

Abstract: Colonic crypt cells possess basolateral Ca(2+)-regulated K+ channels which support Cl- secretion by providing the necessary driving force. The pharmacological characteristics of these channels were examined in Ussing chamber experiments of rat and rabbit colon mucosa by the use of blockers. The chromanol 293B, a blocker of KVLQT1 channels, and clotrimazole (CTZ), a blocker of small Ca(2+)-activated K+ channels, blocked stimulated Cl- secretion completely. Small-conductance Ca(2+)-activated K+ channels (SK) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 23 publications
5
72
0
Order By: Relevance
“…Ca 2ϩ (1 M)-activated hSK4/IK1-like K ϩ currents in T84 cells, in which transcripts of hSK4/IK1 are expressed, have been shown to be blocked by intracellular Ba 2ϩ but not by extracellular Ba 2ϩ (9,23). We also extended the pharmacological study to include 1-EBIO, which has been shown to increase both the heterologously expressed SK4/IK1 (30,32,35,43,51,52) and other native SK4/IK1-like currents (10,32,52). As expected from the striking resemblance between native bovine K Ca and expressed SK4/IK1 currents, the native Ca 2ϩ -activated Rb ϩ currents were modulated by 1-EBIO (Fig.…”
Section: Ajp-cell Physiolmentioning
confidence: 91%
See 1 more Smart Citation
“…Ca 2ϩ (1 M)-activated hSK4/IK1-like K ϩ currents in T84 cells, in which transcripts of hSK4/IK1 are expressed, have been shown to be blocked by intracellular Ba 2ϩ but not by extracellular Ba 2ϩ (9,23). We also extended the pharmacological study to include 1-EBIO, which has been shown to increase both the heterologously expressed SK4/IK1 (30,32,35,43,51,52) and other native SK4/IK1-like currents (10,32,52). As expected from the striking resemblance between native bovine K Ca and expressed SK4/IK1 currents, the native Ca 2ϩ -activated Rb ϩ currents were modulated by 1-EBIO (Fig.…”
Section: Ajp-cell Physiolmentioning
confidence: 91%
“…Recent molecular studies have identified four members (SK1-3 and SK4/IK1) of K Ca channels that form Ca 2ϩ -activated, small-to intermediate-conductance K ϩ channels in various excitable and nonexcitable tissues. SK1-3 channels are predominantly expressed in excitable tissues (50), whereas SK4/IK1 channels are expressed in peripheral nonexcitable cells including secretory epithelia (24,30,31,52), erythrocytes (49), and lymphocytes (32,35). Intriguingly, Jensen et al (30) reported that the highest level of transcripts of hSK4/IK1 was expressed in salivary glands.…”
mentioning
confidence: 99%
“…In order to maintain the membrane potential at rest and during Cl -secretion, K + must be recycled out of the cell across the basolateral membrane [3]. In rat distal colonic epithelia, which is a widely used animal model for the study of intestinal Cl -secretion, the basolateral K + conductance is formed by at least two different types of K + channels, one activated by Ca 2+ -mobilizing secretagogues and the other by cAMP-dependent agonists [4,5]. Several studies have revealed the latter to be KCNQ1, a low-conductance (1-3 pS) basolateral K + channel which is activated during cAMP-stimulated Cl -secretion and inhibited by chromanol 293B and HMR-1556 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Both types take part in Cl -secretion in rat colon: Ca 2+ -dependent rSK4 channels (Warth et al, 1999) and cyclic AMP-activated KCNQ1/KCNE3 channels (Schroeder et al, 2000). Activated channels hyperpolarize (EGTA) free buffer.…”
Section: Discussionmentioning
confidence: 99%